Development of novel structures for enhanced thermal energy storage - Goh, Jian Han (2019)
The aim of this final year project report is to study the effects of different structures on the PCM melting behaviour and to determine the best structure for enhancing the thermal energy storage. In addition, the thermal performance the topologically-optimised structure as compared to conventional Fan-Finned structure is also evaluated. This report examines the latent heat thermal energy storage capabilities of three kinds of structures. These structures are Dendritic-Finned structure, Fan-Finned structure and empty structure. The Dendritic-Finned Structure is developed using the topological optimisation method and is fabricated using the Selective Laser Melting (SLM) technique which is a branch of additively manufacturing technology (also known as 3D-Printing). On the other hand, the Fan-Finned structure is fabricated using conventional fabrication methods such as welding of various thickness of sheet metal together to form the latent heat energy storage device. The Empty structure was fabricated by welding various sheet metals together. However, unlike the Fan-Finned structure, the Empty structure is not designed with any fins. The Empty structure acts as a control specimen in this experimental investigation. The RUBITHERM™ RT35HC Phase Change Material (PCM), which served as the latent heat energy storage medium and composed of a mixture of paraffin waxes, was then poured into these three devices. For this investigation, a 100% PCM filled ratio was used. The Dendritic-Finned structure and Fan-Finned structure were filled with 650 ml of PCM as both the structures were designed to have the same filling ratio in mind. While the Empty structure is filled with 800 ml of PCM. The experiments were conducted under three heat fluxes (7441.86 W/m2, 5271.32 W/m2 and 4186.05 W/m2) applied to the base of each structure. The constant heat flux was generated by an electric heater attached to the base. The results showed that both the Dendritic-Finned and Fan-Finned structures enhance the thermal energy storage performances as compared to the Empty structure. The results obtained also showed that the topologically-optimised Dendritic-Finned structure also produced better melting performances as compared to the conventional Fan-Finned structure. The Dendritic-Finned structure also resulted in a lower wall temperature which corresponds to a lower operating temperature of the heat source. It is also able to melt the same volume of PCM in a more uniformly and within a shorter period as compared to the Fan-Finned structure.